54‐5: Measuring Direct Retinal Projection Displays. Issue 1 (25th September 2020) - Penczek, John; Austin, Richard L.; Obheroi, Sonika; Hasan, Monirul; Cook, Gavin J.; Boynton, Paul A.
Abstract : Direct retinal projection technology is a promising approach that can avoid vergence‐accommodation conflict. But it introduces new measurement challenges. We demonstrate an evaluation system that can perform spatial as well as direct absolute spectral‐based photometric and colorimetric measurements of these devices.